Musical experience from psychological and therapeutic perspective - Paipare, Mirdza (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The author of the paper is a musician, educator and certified music/art therapist. This enables her to view this particular issue both from musicians, teachers and music/art therapist’s view. Within a three-year period research was conducted and the research data on the role of musical emotions in human life were summarised. The research results allow to draw meaningful conclusions on the role of musical emotional experience not only in a person’s life, but also to identify the musical emotions impact on vital areas of human life, concerning the senses, emotions, perception, behaviour, culture, identity. Findings of the study show that scientific application of music provides not only aesthetic, but also educational and even therapeutic effect. Interpretation of the obtained results shows their applicability in pedagogy, psychology, music science, and health care.